IMPROVING METHODOLOGICAL TRAINING OF FUTURE CHEMISTRY TEACHERS BASED ON INTEGRATED EDUCATION - Shirin Khajiyevna Shomurotova (Web of Journals Publishing, 2023)
In this article, the development of chemistry and improvement of methodology, implementation of interdisciplinarity on the basis of integrated education is noted. The importance of using integrated education in pedagogical activity is shown. The role of integrated education for future chemistry teachers is emphasized.
Keywords: chemistry, educational technologies, integrated education, methodology, competence, teaching, educational methods, educational tools.